Pengaruh Computer Self-Efficacy dan Task-Technology Fit Terhadap penerimaan Penggunaan lnternet - Petra Surya Mega Wijaya (Fakultas Bisnis UKDW, 2006)
This study examines the correlation between'perceived ease-of-use uari-. able and perceived usefulness variable, beliefs (perceived ease:of-use and perciived usefulness) against behavior intention to !t:e, behavior inteition to use against behavior to use, cornputer self efricaW against perceived e^